2016
DOI: 10.4236/aim.2016.69070
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spent Craft Brewers’ Yeast on Fermentation and Methane Production by Rumen Microorganisms

Abstract: Saccharomyces cerevisiae is a key component of beer brewing and a major by-product. The leftover, spent brewers' yeast from large breweries has been used as a protein supplement in cattle; however the possible advantages of spent yeast from smaller craft breweries, containing much higher levels of bioactive hop acids, have not been evaluated. Hops secondary metabolites from the hops (Humulus lupulus L.) used to make beer are concentrated in the yeast during brewing, and have antimicrobial activity against Gram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…There is interest in brewery ruminant co-products with high levels of hop phytochemicals. Some results have shown that spent brewers' yeast inhibited rumen ammonia and methane production [25] [26]. Another DOI: 10.4236/aim.2019.912063 990 Advances in Microbiology study indicates that older stored hops are adequately antimicrobial for feeding applications even after they are no longer desirable by brewers [27].…”
Section: Discussionmentioning
confidence: 99%
“…There is interest in brewery ruminant co-products with high levels of hop phytochemicals. Some results have shown that spent brewers' yeast inhibited rumen ammonia and methane production [25] [26]. Another DOI: 10.4236/aim.2019.912063 990 Advances in Microbiology study indicates that older stored hops are adequately antimicrobial for feeding applications even after they are no longer desirable by brewers [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, hops bitter acids inhibit rumen methane production, as well [4]. Even residual hop acids in spent craft brewers' yeast inhibited methane production [23] and ammonia production [24]. It is highly likely that older hops will also inhibit methane.…”
Section: Discussionmentioning
confidence: 99%
“…Embora os óleos essenciais sejam os aditivos não antibióticos mais comuns, há outras opções que podem ser utilizadas com a mesma finalidade, como as leveduras e os probióticos. Neste contexto, Pszczolkowski et al (2016) avaliaram a eficácia da ação antimicrobiana dos ácidos α e β do lúpulo (Humulus lupulus L.), compostos presentes nas leveduras do resíduo de cervejaria. Para avaliação foram incubadas amostras de feno de gramíneas com líquido ruminal proveniente de cabras, em um dos líquidos havia a presença de leveduras do resíduo de cervejaria enquanto no outro apenas leveduras isentas dos ácidos.…”
Section: Alternativas Nutricionais Não Antibióticasunclassified